LINGUISTICS AND LITERACY: A NEW UNDERSTANDING - Palmer, Joe Darwin (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1988)
A great literacy debate has been going on for some time, yet the debaters cannot agree on what they are talking about. The English teaching profession is in despair. Reading alone has not been proven to lead to higher order cognitive skills. The acquisition of print literacy has not unfailingly led to social betterment and progress. Work on literacy should be informed by many disciplines, and especially by linguistics in which recent research on language in use is revealing definitions, and facts and insights into the nature of literacy. RÉSUMÉ Un grand débat sur l’alphabétisme est en cours depuis quelque temps déjà et pourtant personne ne s’entend même à convenir sur ce qui fait l’objet du débat. Les professeurs d’anglais sont au d’sespoir. Il n’a pas été prouvé que la seule lecture favorisait le développement d’aptitudes cognitives supérieures. L’apprentissage de la lecture et de l’écriture n’est pas toujours associé à l’amélioration sociale et au progrès. Les recherches sur l’alphabétisme doivent refléter de nombreuses disciplines, particulièrement la linguistique où les recherches récentes sur la langue en usage révèlent des définitions, des faits et des aperçus sur la nature de l’alphabétisme.